Use of the exergy method to assess the energy efficiency of technical facilities - Zhukov Vladimir; Erofeev Leonid; Peresezkij Ilya (E3S Web of Conferences, 2022)
Improvement of technical objects and systems energy efficiency, the most widespread of which are heat engines, is an urgent task, for the solution of which it is necessary to use various methods. The review of scientific publications allows to single out the exergic analysis based on the exergic balance of power installations of different purpose and design as one of the basic universal methods of energy efficiency estimation. Substantiation of universality of the exergic analysis method on the basis of its theoretical preconditions is given. The basic reserve of increase in power efficiency of thermal engines is the rational use of secondary power resources. With the purpose of an estimation of prospects of use of power resources of heat-carrying agents of cooling systems) the calculation of the heat pump working on a reverse Rankine cycle is executed. On the basis of the executed calculations, the conclusion about prospects of use of the given devices, including for replacement of independent boilers in ship power installations is made. The article contains proposals on use of the exergic method in a complex with traditional methods of estimation of power efficiency of complex technical systems. Advantages of such approach are shown, its possibilities and perspective fields of application are determined. The data obtained as a result of conducted research shows that the use of secondary energy resources of heat engines with the use of recycling turbines and heat pumps of modern designs is promising and allows increasing the fuel utilization factor of reciprocating and gas turbine engines.